2019
DOI: 10.21037/jtd.2019.06.56
|View full text |Cite
|
Sign up to set email alerts
|

A quality assessment of evidence-based guidelines for the prevention and management of ventilator-associated pneumonia: a systematic review

Abstract: Background: Numerous evidence-based guidelines (EBGs) pertaining to ventilator-associated pneumonia (VAP) have been published by domestic and international organizations, but their qualities have not been reported. Methods: A systematic search of the literature was performed up to July 2018 for relevant guidelines. Guidelines were eligible for inclusion if they incorporated recommendation statements for prevention and/ or management in adults or children with VAP and were developed on a systematic evidence-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…The results of the present study showed that VAP is highly prevalent in ICU patients, and most of the organisms causing pneumonia are gram-negative bacteria, which have very high antibiotic resistance and are resistant to almost most commonly used antibiotics in the ICU. Among these, Acinetobacter, which is highly prevalent, has multidrug resistance, and among the antibiotics studied, only colistin was able to somewhat control the growth of the bacterium and the prevalence of pneumonia caused by this bacterium was high, similar to other studies in the ICUs (5,6). Consistent with the results obtained in the present study, Ahsan et al (2016) also reported that the most prevalent microorganisms isolated from the culture of tracheal secretions were gram-negative bacteria (76.13%), followed by fungal pneumonia (17.04%) and finally gram-positive bacteria (6.81%).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results of the present study showed that VAP is highly prevalent in ICU patients, and most of the organisms causing pneumonia are gram-negative bacteria, which have very high antibiotic resistance and are resistant to almost most commonly used antibiotics in the ICU. Among these, Acinetobacter, which is highly prevalent, has multidrug resistance, and among the antibiotics studied, only colistin was able to somewhat control the growth of the bacterium and the prevalence of pneumonia caused by this bacterium was high, similar to other studies in the ICUs (5,6). Consistent with the results obtained in the present study, Ahsan et al (2016) also reported that the most prevalent microorganisms isolated from the culture of tracheal secretions were gram-negative bacteria (76.13%), followed by fungal pneumonia (17.04%) and finally gram-positive bacteria (6.81%).…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, others also consider the incidence of lung infection within the first 24 hours as VAP (4). This sensitivity to distinguish this pneumonia from other lung infections is because hospital pathogens such as Pseudomonas aeruginosa, Acinetobacter baumannii or methicillin-resistant Staphylococcus aureus are resistant to some or all of the antibiotics, and the resulting infections lead to increased mortality rate in 13-25.5% of patients (5,6). Prolonged length of hospital stay increases the hospital costs (7).…”
mentioning
confidence: 99%
“…3)patients suspected of infectious disease requiring microbiological investigations [2,11]. 2)patient unable to ful ll the required medical follow-up;…”
Section: Inclusionmentioning
confidence: 99%
“…2)patients with mechanical ventilation, the expected mechanical ventilation duration was more than 48 hours [2];…”
Section: Inclusionmentioning
confidence: 99%
“…In the intensive care unit (ICU), severe pneumonia diagnosis is particularly complex due to the similar clinical symptoms. It generally leads to the dysfunction of other organs and thus carries high mortality [1][2][3]. So it is critical to provide an effective symptomatic treatment early.…”
Section: Introductionmentioning
confidence: 99%